Risk Perception, Risk Communication, and Mitigation Actions of Flash Floods: Results from a Survey in Three Types of Communities - Ming Zhong (MDPI AG, 2021)
In order to improve the decision-making of risk management and enhance community resilience to flash floods, the perception of risks, communication of warnings, and mitigation actions concerning flash floods were investigated in this study. The survey involves 280 participants from three types of communities in flash flood-prone areas. Results show that: (i) About 55.4% of community participants misperceived or underestimated the risk of flash floods, especially in the suburban communities, and people had misconceptions about the safety of crossing fast-flowing water, even though most of them had experienced flash flood hazards. (ii) In total, 67.9% of participants indicated that they had at some point received a flash flood warning. The perception of accuracy was related to trust in flash flood warnings, but they were different constructs for some individuals. Moreover, residents in the rural community and suburban community reported a closer social communication with neighbors, which would greatly influence inhabitants’ attitudes and behaviors towards the flash flood warnings and mitigation actions. (iii) Most of the participants indicated they would take some protective action when they received a warning. Risk perceptions and risk communications influence the mitigation actions in the community. Significant variables in the rural community and non-rural community were explored, and some important suggestions are highlighted. These findings suggest that risk perception and risk communication in neighborhoods help people to decide what action to take in the given scenarios, contribute to enhancing the community resilience, and contribute to coping with future flash floods in a more specific and effective way.